2019
DOI: 10.1080/10503307.2019.1566676
|View full text |Cite
|
Sign up to set email alerts
|

The dose-response effect in routinely delivered psychological therapies: A systematic review

Abstract: The dose-response effect refers to the relationship between the dose (e.g., length, frequency) of treatment and the subsequent probability of improvement. This systematic review aimed to synthesise the literature on the dose-response effect in routine psychological therapies delivered to adult patients with mental health problems. Twenty-six studies were eligible for inclusion. Different methodological approaches have been used to examine the dose-response effect; including survival analysis, multilevel modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
105
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 43 publications
15
105
0
2
Order By: Relevance
“…Conversely, extending therapy beyond these dose‐response intervals (up to 24 sessions; Robinson, Delgadillo, & Kellett, 2020) is warranted for patients who have shown signs of RCSI, and we strongly caution against the arbitrary restriction of treatment sessions for these cases. Prior research has shown that IAPT services that offer a low mean number of treatment sessions tend to attain poorer clinical outcomes (Clark et al, 2018), and therefore offering an adequate dose of therapy is central to effective and ethical practice (National Collaborating Centre for Mental Health, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, extending therapy beyond these dose‐response intervals (up to 24 sessions; Robinson, Delgadillo, & Kellett, 2020) is warranted for patients who have shown signs of RCSI, and we strongly caution against the arbitrary restriction of treatment sessions for these cases. Prior research has shown that IAPT services that offer a low mean number of treatment sessions tend to attain poorer clinical outcomes (Clark et al, 2018), and therefore offering an adequate dose of therapy is central to effective and ethical practice (National Collaborating Centre for Mental Health, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First, compared to IAPT recovery rates which classify cases based on symptomatic reductions below the cut‐offs for PHQ‐9 and GAD‐7 (National Collaborating Centre for Mental Health, 2018), the strict RCSI criteria applied in this study additionally requires the observation of statistically reliable improvement and therefore yields more conservative estimates of treatment response. As shown in a methodological review on this topic (Robinson, Delgadillo, & Kellett, 2020), studies that use RCSI criteria (rather than more lenient indices of improvement) tend to yield lengthier dose‐response parameters which are less likely to classify cases that take longer to benefit from therapy as nonresponders. Second, we report RCSI rates separately for low and high intensity interventions, whereas IAPT recovery rates reflect improvements observed during the whole stepped care treatment pathway starting with an initial (pretreatment) assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of replicated findings in different studies indicate that the optimal dose of low intensity CBT interventions is between 4 and 6 sessions (Delgadillo et al, 2014, Delgadillo, Kellett, et al, 2016Firth et al, 2015). A recent systematic review of this literature concluded that the probability of symptomatic remission is minimal in cases that access less than 4 sessions of low intensity CBT interventions (guided self-help), thus offering an evidence-based criterion to define adequate attendance (Robinson, Delgadillo, & Kellett, 2019). We considered that attendance of all 6 sessions was too strict a criterion to denote adequate engagement with SC, since it is common that patients miss one or two sessions due to practical obstacles such as work or childcare commitments, so our definition of adequate attendance is in line with the current evidence-base for the minimum recommended number of sessions for low intensity CBT (Robinson et al, 2019).…”
Section: Methodsmentioning
confidence: 99%